Regulasi dan Kebijakan yang Mengatur Lembaga Keuangan Syariah di Indonesia - Dara Tsanya Abdul Rohim; Ranti Dwi Aryanti; Cantika Cantika; Ryan Cahya Nugraha; Joni Joni; Raihani Fauziah (STAI YPIQ BAUBAU, SULAWESI TENGGARA, 2025)
. Sharia financial institutions in Indonesia have experienced significant growth in line with increasing public demand for financial systems that comply with sharia principles. This growth requires clear regulations and policies to create stability, legal certainty, and protection for customers. This article examines the dynamics of regulations governing Islamic financial institutions, from the initial role of Bank Indonesia (BI) to the establishment of the Financial Services Authority (OJK) as the main supervisory and regulatory agency. In addition, this article also discusses the contribution of the National Sharia Council–Indonesian Ulema Council (DSN-MUI) in issuing fatwas that form the basis for the operation of Islamic products and services. With the Financial Services Authority Regulation (POJK) and other related regulations, the supervision of Islamic financial institutions has become more integrated, effective, and adaptive to industry developments. This study confirms that the existence of comprehensive regulations and policies not only strengthens the governance of Islamic financial institutions but also encourages the growth and competitiveness of the Islamic financial industry at both the national and global levels.